2017
DOI: 10.1002/ece3.2767
|View full text |Cite
|
Sign up to set email alerts
|

Timing of nest vegetation measurement may obscure adaptive significance of nest‐site characteristics: A simulation study

Abstract: Advances in understanding avian nesting ecology are hindered by a prevalent lack of agreement between nest‐site characteristics and fitness metrics such as nest success. We posit this is a result of inconsistent and improper timing of nest‐site vegetation measurements. Therefore, we evaluated how the timing of nest vegetation measurement influences the estimated effects of vegetation structure on nest survival. We simulated phenological changes in nest‐site vegetation growth over a typical nesting season and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 40 publications
2
43
1
Order By: Relevance
“…While our analyses revealed mixed support for relationships between grass height and nest survival in sage‐grouse, they confirmed recent findings that associations between herbaceous vegetation structure and nest success are frequently byproducts of temporally biased sampling rather than indicative of effect of concealing cover on detectability by predators (Gibson, Blomberg, et al., ; McConnell et al., ). Sampling vegetation following nest fate, a pervasive practice in studies of sage‐grouse and other ground‐nesting birds, consistently produces spurious relationships between grass height and nest survival and should, therefore, be avoided.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While our analyses revealed mixed support for relationships between grass height and nest survival in sage‐grouse, they confirmed recent findings that associations between herbaceous vegetation structure and nest success are frequently byproducts of temporally biased sampling rather than indicative of effect of concealing cover on detectability by predators (Gibson, Blomberg, et al., ; McConnell et al., ). Sampling vegetation following nest fate, a pervasive practice in studies of sage‐grouse and other ground‐nesting birds, consistently produces spurious relationships between grass height and nest survival and should, therefore, be avoided.…”
Section: Discussionsupporting
confidence: 85%
“…Recent evidence has demonstrated that the positive association between grass height, a commonly used metric of herbaceous concealing cover among sage‐grouse nesting studies, and nest survival may be indicative of biased methods rather than a causal relationship (Gibson, Blomberg, et al., ; McConnell et al., ). Using both empirical and simulation approaches, it has been shown that measuring grass height at nests following nest fate (i.e., hatch or failure) produces inflated or even spurious statistical relationships between grass height and nest survival.…”
Section: Introductionmentioning
confidence: 99%
“…We sampled vegetation characteristics within 3 days after of the estimated hatch date or date of brood use to reduce biases associated with changes in vegetation growth (McConnell et al ). To quantify vegetation associated with daytime use sites, we downloaded GPS locations every 3 days and randomly selected 1 location from the day of our most recent brood survey to visit and sample.…”
Section: Methodsmentioning
confidence: 99%
“…We used conditional logistic regression implemented via the clogit function in the package survival (Therneau ) to compare ptarmigan nest or brood use locations (case) to dependent random available locations (control). We were cognizant that vegetation can change over time (i.e., added growth or senescence), and when estimating covariate effects on nest survival, inconsistent timing of measurements can result in biased assessment of those effects on survival (Gibson et al , McConnell et al ). We did not measure vegetation at projected hatch dates as is suggested for nest survival analyses (Gibson et al , McConnell et al ), but we measured vegetation at dependent random sites immediately following measurements at the respective use site (typically within a day or 2 of use), directly comparing vegetation available to females within a given area at that given time (Prima et al ).…”
Section: Methodsmentioning
confidence: 99%